Demons and the Devil in ancient and medieval Christianity - Vos, Nienke; Otten, Willemien (Supplements to Vigiliae Christianae, 2011)
This collection of essays analyzes the role of demons and the devil in ancient and medieval Christianity. Proceeding from a variety of scholarly perspectives-historical, philosophical and theological, as well as philological, liturgical and theoretical-the volume's diverse approach matches the complexity of its chosen theme.